Prevalence,antibiotic susceptibility profiles and ESBL production in Klebsiella pneumoniae and klebsiella oxytoca among hospitalized patients - Sourav, Chakrabarty; Mohsina, Kaniz; Kumar Sarker, Palash; Alam, Md Zahangir; Abdul Karim, Mohamed Ismail; Abu Sayem, S.M (Croatian Society of Natural Sciences, 2016)
Background and Purpose: Klebsiella pneumoniae and Klebsiella oxytoca are the two most common pathogens causing nosocomial infections in humans and are of great concern for developing multidrug resistance. In the present study, K. pneumoniae and K. oxytoca from clinical samples were evaluated for their antibiotic sensitivity patterns against commonly used antibiotics and production of extended-spectrum beta-lactamase (ESBL). Materials and Methods: The isolates were obtained from tracheal swabs, sputum, wound swabs, pus, blood and urine samples of hospitalized patients. Klebsiella pneumoniae and Klebsiella oxytoca were identified by cultural and biochemical methods. Antibiotic sensitivity test was performed by modified Kirby-Bauer disc diffusion technique. ESBL production in Klebsiella spp. was confirmed by double disc synergy test. Results and Conclusion: Out of 500 clinical isolates, 120 were found positive for Klebsiella among which 108 were K. pneumoniae and 12 were K. oxytoca based on indole test. Prevalence rate of Klebsiella was found more prominent in males aged over 50 years, mostly in urine samples. Overall resistance pattern of Klebsiella isolates to ampicillin,amoxicillin, ceftriaxone, ciprofloxacin, co-trimoxazole, gentamicin, nalidixic acid,ttracycline was 100%, 90%, 45%, 40%, 45%, 25%, 50%, 35% respectively. Multidrug resistance was found more common in K. pneumoniae (56%) than in K. oxytoca (50%). Prevalence rate of ESBL producing Klebsiella was found 45% among which K. pneumoniae (50%) were found more prominent than K. oxytoca (25%). All the ESBL producing Klebsiella isolates were found to be multidrug resistant, showing 100% resistance to Ampicillin,Amoxicillin,Ceftriaxone and Ciprofloxacin.